2010
DOI: 10.3928/15428877-20101124-16
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-Domain Optical Coherence Tomography Imaging of Gas Tamponade Following Macular Hole Surgery

Abstract: In this prospective study, the authors report fourier-domain optical coherence tomography (FD-OCT) imaging of gas-inner retinal tamponade following surgery for full-thickness macular hole and evaluate postoperative posturing based on FD-OCT findings. Patients underwent FD-OCT 1 day after pars plana vitrectomy, internal limiting membrane peel, and gas injection. Three-dimensional FD-OCT and high-resolution line scans demonstrated gas-inner retinal tamponade across the macula with the apex of tamponade located a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…[121][122][123][124] A recent study using spectraldomain optical coherence tomography (OCT) to capture hole closure showed that following vitrectomy with ILM peeling and gas tamponade, 77% closure rate was achieved as fast as on postoperative day 1. 126 This supports the idea of using a gas with shorter intraocular longevity such as air, and obviates the need for posturing. 126 This supports the idea of using a gas with shorter intraocular longevity such as air, and obviates the need for posturing.…”
Section: Macular Holesupporting
confidence: 57%
“…[121][122][123][124] A recent study using spectraldomain optical coherence tomography (OCT) to capture hole closure showed that following vitrectomy with ILM peeling and gas tamponade, 77% closure rate was achieved as fast as on postoperative day 1. 126 This supports the idea of using a gas with shorter intraocular longevity such as air, and obviates the need for posturing. 126 This supports the idea of using a gas with shorter intraocular longevity such as air, and obviates the need for posturing.…”
Section: Macular Holesupporting
confidence: 57%
“…28,29 Additionally, OCT data have shown that hole closure occurs as early as 24 hours into the postoperative course. 30 32 This furthers the case against long periods of postoperative FDP.…”
Section: Cons Of Fdpmentioning
confidence: 88%